SENI, SIMBOL, DAN KESAKRALAN: ANALISIS ESTETIKA PADA TRADISI NGAYU-AYU DI DESA SEMBALUN - Kasim, Sunardy; Syamsurrijal, Syamsurrijal; Hadirman, Hadirman (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
The Ngayu-Ayu tradition in Sembalun Village is one of the oldest agrarian rituals in Sasak culture, performed every three years as an expression of gratitude for the fertility of the land, a ward off disaster, and a restoration of harmony between humans and nature. This study aims to examine how elements of art, symbolism, and sacredness work together to shape the collective aesthetic experience of this ritual. Using an interpretive qualitative approach that combines ethnography, aesthetic phenomenology, and semiotic analysis, this study collected data through participant observation, in-depth interviews, and visual and material documentation. The theoretical framework employed encompasses the aesthetics of Baumgarten, Kant, Hegel, Eastern aesthetics, and Merleau-Ponty's theory of the phenomenology of the body. The analysis reveals that the aesthetic structure of Ngayu-Ayu is formed through four main domains. First, visual aesthetics is evident in the composition of offerings, the use of organic materials, and the arrangement of colors and shapes that create sensory harmony and represent an agrarian cosmology. Second, performative aesthetics are manifested through ritual movements, gendang beleq music, and collective rhythms that create a shared bodily experience and strengthen social cohesion. Third, the ritual's symbolic structure demonstrates the interaction of icons, indices, and symbols that negotiate the relationship between humans, nature, and ancestors. Fourth, the sacred dimension is present through the experience of the sublime and the principle of cosmic harmony, linking aesthetic values with ecological ethics. This study concludes that Ngayu-Ayu is a living art that combines aesthetic expression, symbolic meaning, and ecological spirituality. This ritual functions as a cultural mechanism that maintains the continuity of identity, community morality, and the sacred relationship between humans and nature. This study contributes to the development of Nusantara aesthetic studies and offers an alternative perspective in understanding ritual art as a practice of knowledge and cultural resilience.